Medioevo e medievalismo tra Europa e America. L’attualità di un dibattito antico - Montesano, Marina (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2016)
Where and when does our idea of the Middle Ages begin? The success of literary works in which the fantastic component is the backbone of an imaginary Middle Ages (let’s think about Tolkien or Martin) is rooted in the Anglo-Saxon tradition, then exported to the United States, where since the Eighteenth Century we can notice the development of a strong revival of Gothic style: hence it springs an idea, more or less historically founded, of Middle Ages. In the link between historical and fictitious reconstructions, North American architecture is a sort of petrified discussion about the problem of our perception of Gothic and, more generally, of an epoch whose fundamental characters are still subject to debate. Keywords: Middle Age; Gothic style; Tolkien; Martin; American architecture.